Sosialisasi Penggunaan Media Pembelajaran Pohon Angka Berbasis ICT Bagi Guru-Guru di SD Negeri 1 Kualasimpang - Warsinah Warsinah (Jurnal Kabar Masyarakat, 2023)
In essence, elementary school phase A is a place where children play while studying or learn while playing. Therefore, every lesson must be fun and appropriate to the child's growth and development stage. One way that teachers can do this is by using ICT-based number tree media. The benefit of number tree media is that it sharpens children's brains, here it can be seen when children arrange numbers according to their sequence, training eye and hand coordination. Along with developments in the times and future education, the use of ICT must start from early childhood. Mastery of ICT should also be the basic essence of filling a life that is growing and developing. For this reason, phase A elementary school teachers should adhere to the principles of early childhood education in designing teaching development programs that involve ICT. In this service activity, the problem is the low understanding of teachers at SD Negeri 1 Kualasimpang regarding the use of ICT-based learning media. The solution provided by the service team is the socialization of the use of ICT-based number tree learning media. The result of this service is that there is an increase in knowledge for teachers regarding the use of ICT-based number tree learning media.